LITERATUR REVIEW: PENGARUH ASI EKSLUSIF TERHADAP KEJADIAN STUNTING PADA BALITA - Awwalin, Jamilatul; Munir, Zainal (Jurnal Keperawatan Profesional, 2023)
Stunting is one of the nutritional problems of toddlers with growth failure that has accumulated since before and after birth caused by inadequate intake of nutrients. Short toddlers (stunting) can be detected when a toddler has been measured for length or height, then compared with nutritional status based on length or height according to age when compared to the 2005 WHO-MGRS standard, the z-score value is less than -2SD and categorized as very short if the z-score is less than -3SD (Ministry of Health, 2016). Objective: To find out the effect of "The Effect of Exclusive Breastfeeding on Stunting Incidents in Toddlers". Methods: Database searches include Google Scholar, Science Direct and Proquest with the keywords Exclusive Breastfeeding, Stunting, and Toddlers. Results: The analysis of 15 shows that there is an influence of Gadget Addict against adolescent deviant behavior. Conclusion : The results of the research from the literature review show that there are "The Influence of Exclusive Breastfeeding on Stunting Incidences in Toddlers" : With the average results of the journal showing a relationship between exclusive breastfeeding and the incidence of stunting. It was found that a history of exclusive breastfeeding and a history of energy intake were factors in the incidence of stunting.